Implementasi Kebijakan TPPK dalam Pencegahan Bullying di Sekolah Dasar Kecamatan Samarinda Ilir - Butar Butar, Gita Taruli; Khotimah, Khusnul (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Bullying remains a prevalent form of violence in Indonesian elementary schools. It has a serious impact on students' psychological and academic development. To prevent this, the government issued Ministerial Regulation No. 46 of 2023 concerning the prevention and handling of violence in educational units. This regulation requires every school to form a Violence Prevention and Handling Team (TPPK). This study aims to analyse the implementation of the TPPK policy in preventing bullying in primary schools in Samarinda Ilir district. A descriptive qualitative approach was used for this study, employing data collection techniques such as in-depth interviews, participatory observation and documentation studies. The findings indicate that, while most schools have established a TPPK, its implementation is suboptimal. Barriers include limited understanding of the policy, minimal training, insufficient human resources and budget, and the absence of a structured evaluation system. However, positive initiatives include collaboration with parents and external institutions. The study was analysed using George C. Edwards III's policy implementation theory. The study's implications demonstrate the importance of continued support from the education office, integrated training for TPPK members and the reinforcement of an anti-violence culture in schools. It is expected that this research will contribute to the strengthening of educational policy management based on student protection.